Constructed floating wetlands: a "safe‐to‐fail" study with multi‐sector participation. Issue 1 (24th April 2022) - Rottle, Nancy; Bowles, Mason; Andrews, Leann; Engelke, Jennifer
Abstract : The Duwamish River Floating Wetlands project designed, built, and deployed constructed floating wetlands in the estuary of the urban Duwamish River in Seattle, Washington, during the 2019 and 2020 outmigration seasons for juvenile salmon. Using a "safe‐to‐fail" methodology and adaptive management strategies, these innovative floating wetland prototypes were custom designed to provide the native plants, invertebrates and slow water habitat that juvenile salmon require during their transition from fresh to salt water, and were monitored for these outcomes. This paper will provide insight into the prototype designs, adaptive management strategies and plant performance, and unique public‐private‐academic‐community partnerships that supported 2 years of design and research.